Exploring the hurdles of implementing National School Health Policy in Namibian Schools: insights from stakeholders - Ndasilohenda Katangolo-Nakashwa; Faniswa Honest Mfidi (BMC Health Services Research)
Abstract This qualitative research study explores stakeholders’ perspectives on the challenges of implementing Namibia's National School Health Policy (NSHP) in schools. The interview guide used for this study was specifically developed to address the research objectives and themes. A total of 20 stakeholders participated, including educators, nurses, principals, and health program administrators from three regions in Namibia. The study identifies significant barriers to effectively implementing the school health policy. These barriers include staffing shortages, inadequate resources, limited learner awareness of health rights, and insufficient teacher well-being. Additional challenges involve resource constraints, a lack of monitoring and evaluation, and limited coordination between the education and health sectors. The thematic analysis reveals recurring patterns and emphasizes the need for increased resource allocation, comprehensive training, collaborative policy development, and initiatives to improve teacher well-being. These findings provide valuable insights for refining future implementation strategies for school health programs in Namibia, highlighting the importance of strong leadership, stakeholder involvement, and adequate funding to support the goals of the NSHP.